The Prevalence and Impact of Body Mass Index Category in Patients with Acute Myocardial Infarction - Anggoro Budi Hartopo; Vina Yanti Susanti; Budi Yuli Setianto (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2016)
Background: Body mass index is widely recognized as a tool to classify obesity and adiposity. In Asian population, body mass index category can be divided as underweight, normal, overweight and obese. The prevalence of this categorisation is varied among patients with acute myocardial infarction. Furthermore, there is a J and U curve relationship between body mass index category with outcome in acute myocardial infarction. This research aims to investigate the prevalence of body mass index category and its impact on patients with acute myocardial infarction.Methods: The research design is a cross sectional study. The subjects of this research are patients hospitalised with acute myocardial infarction. Subjects are categorised as underweight, normal, overweight and obese, based on Asian body mass index categorisation. The demography, clinical and laboratory data is compared among categories and statistically analysed. The major adverse cardiac events occuring during hospitalisation are recorded and its incidence is compared among group. A p value < 0.05 is statistics limit for significance.Results: We analyse 375 subjects hospitalised with acute myocardial infarction. The most prevalence BMI category is overweight (47.7 %), the second most common category is normal (33.1 %), followed by obese (15.5 %) and the least common category is underweight (3.7 %). No significant difference is observed in respect of gender and cardiovascular risk factors. The underweight subject is significantly older as compared to other categories. The glucose level and atherogenic lipid tend to be higher in underweight subject as compared with normal subject. There is no difference in the incidence of major adverse cardiac events among body mass index categorisation.Conclusion: The overweight is the most common body mass index category in acute myocardial infarction. The underweight subject is significantly older and tend to have worse biochemical parameters as compared to other categories. The incidence of MACE is not associated with the body mass index category.Keywords: body mass index; overweight; underweight; acute myocardial infarction